New radio continuum study of the large magellanic cloud supernova remnant N49 - Ghavam, Maddie; Filipović, Miroslav D.; Alsaberi, Rami; Barnes, Luke; Crawford, Evan J.; Haberl, Frank; Kavanagh, Patrick; Maggi, Pierre; Payne, Jeffrey; Rowell, Gavin; Hidetoshi, Sano; Sasaki, Manami; et al. (Publications of the Astronomical Society of Australia, 2024)
We present new Australia Telescope Compact Array (ATCA) radio observations towards N 49, one of the brightest extragalactic supernova remnants (SNRs) located in the Large Magellanic Cloud (LMC). Our new and archival ATCA radio observations were analysed along with Chandra X-ray data. These observations show a prominent ‘bullet’ shaped feature beyond the southwestern boundary of the SNR. Both X-ray morphology and radio polarisation analysis support a physical connection of this feature to the SNR. The ‘bullet’ feature’s apparent velocity is estimated at ∼1 300 km s−1, based on its distance (∼10 pc) from the remnant’s geometric centre and estimated age (∼7 600 yr). we estimated the radio spectral index, α = −0.55 ± 0.03 which is typical of middle-age SNRs. Polarisation maps created for N 49 show low to moderate levels of mean fractional polarisation estimated at 7±1% and 10±1% for 5.5 and 9 GHz, respectively. These values are noticeably larger than found in previous studies. Moreover, the mean value for the Faraday rotation of SNR N 49 from combining CABB data is 212±65 rad m−2 and the maximum value of RM is 591±103 rad m−2.
CRIS-Team Scopus Importer:2024-12-06
Keywords: (galaxies:) Magellanic Clouds; ATCA; ISM: supernova remnants; radio continuum: ISM